Variabilidade Interanual da Pressão Atmosférica Associada ao Fenômeno El Niño Oscilação Sul em Santa Maria, RS - Gabriel, Luana F.; Uhlmann, Lilian O.; Ferraz, Simone E. T.; Streck, Nereu A.; Heldwein, Arno B. (Ciência e Natura, 2011)
.